The native fish diversity with environmental influencing factors in the Daqing River basin, China - Zhou, Xushen; Li, Yanqing; He, Jianwu; Hou, Yin; Wang, Fei (Frontiers in Environmental Science, 2024)
Investigating and assessing native fish diversity and conducting regional assessments of threats are vital for the conservation of aquatic biodiversity. For this specific study, the Daqing River basin in China was chosen as the research area. Field surveys were carried out between 2018 and 2019, supplemented by a review of pertinent literature and other records. The findings revealed that 85 fish species have been recorded in the basin, consisting of 78 freshwater species categorized into 8 orders, 17 families, and 59 genera, among which Cypriniformes comprised 64% of the total catch. The low proportion of threatened and endemic species was an important feature of the fish diversity of the Daqing River. Despite the theoretical presence of 85 species, field surveys managed to collect only 42 species, of which 33 were confirmed as naturally occurring within the basin. The average values of Margalef richness index, 22 ShannonWiener diversity index and Pielou evenness index were 1.72, 2.04 and 0.80 respectively,signifying a low fish diversity with relatively uniform distribution across the sampled regions. This study found that the community structure and diversity of fish were closely related to environmental factors, particularly water quality. Among these factors, ammonia nitrogen emerged as a significant determinant of fish diversity. High concentrations of ammonia nitrogen inhibit fish growth, endanger health, and can even lead to death. Additionally, dams and other water infrastructure also impact fish community structure and diversity. This baseline study can provide a basis for the protection and ecological restoration of fish resources in the Daqing River.